ACCOUNTING AND FISCAL ASPECTS RELATED TO CONSTRUCTIONS AND LAND - Marcela BENGESCU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
This paper approaches aspects related to the value added tax in the case of operations with real property. The presentation of the theoretical notions and the applications are grouped on types of operations: exempt from VAT; voluntarily liable to pay VAT, and liable to pay VAT under the law. The analysed taxpayers were mainly legal entities that carry out business subject to VAT. A small percentage is represented by information related to non-taxable natural persons trading in real property.